Perception of sound : how much does quality cost? - Lim, Miracle Joseph Jia Yi. (2013)
The report shows results from an investigation into the perception of sound and explores the relationship between price and perceived quality of earphones. People tend to rate the quality of music listening experiences in terms of sonic clarity and envelopment [1]. Today, the most common situation where people listen to music is while commuting [2], however such environments are far from ideal because of the generally high ambient noise levels.